The study on determinants of non-performing loan in Malaysia / Muhamad Fikri Sanusi - Sanusi, Muhamad Fikri (Faculty of Business and Management, 2018)
The purpose of this study is to examines either the non-performing loan is affected by the macroeconomic variables such as average lending interest rate, unemployment rate, inflation rate, and real GDP growth. Due to the economic crisis, many banking industry in many countries affected with it by showing the rising number of non-performing loan. Regarding on that, this study will study and explained more the relationship between the macroeconomic variables and non-performing loan in Malaysia. The data collected for this is in quarterly and monthly basis. Later on, the data in monthly basis is converted into data quarterly data by using E-views as this study is choosing the quarterly data for the period of 2000 Q1 until 2009 Q4. In the process of findings, a few test has been conducted by using E-views. Based on the result, only one independent variable has been found to have insignificant impact on the non-performing loan which is average lending interest rate. Meanwhile, another three variables has shown an significant impact towards the dependent variables.